2022
DOI: 10.3389/fmars.2022.958197
|View full text |Cite
|
Sign up to set email alerts
|

Plastic additive di(2-ethylhexyl)phthalate (DEHP) causes cell death and micronucleus induction on a bottlenose dolphin’s (Tursiops truncatus) in vitro-exposed skin cell line

Abstract: Marine plastic pollution is one of the most concerning worldwide environmental issues, and research is day by day demonstrating its adverse effects on marine ecosystems. Nevertheless, little is still known about the toxic potential on marine fauna of chemical additives released by plastic debris. Here we investigated the cyto- and genotoxicity of the most used plasticizer in plastic production, di(2-ethylhexyl)phthalate (DEHP), on a skin cell line (TT) derived from the bottlenose dolphin (Tursiops truncatus), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…However, it is well known that different cell types react to xenobiotics like microplastics, 80,81 and additives cause cell death and micronucleus induction. 82 Microplastics are frequently described as the "cocktail of contaminants" because of their link to additives, medications, heavy metals, pesticides, and other persistent organic pollutants that are found in the environment. 83,84 It has been demonstrated that when the plastic material's properties deteriorate with age as a result of exposure to high temperatures, especially UV radiation, the additives are released into the environment at an increased rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well known that different cell types react to xenobiotics like microplastics, 80,81 and additives cause cell death and micronucleus induction. 82 Microplastics are frequently described as the "cocktail of contaminants" because of their link to additives, medications, heavy metals, pesticides, and other persistent organic pollutants that are found in the environment. 83,84 It has been demonstrated that when the plastic material's properties deteriorate with age as a result of exposure to high temperatures, especially UV radiation, the additives are released into the environment at an increased rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that different cell types react to xenobiotics like microplastics, 80,81 and additives cause cell death and micronucleus induction. 82…”
Section: Discussionmentioning
confidence: 99%
“…In the marine environment, marine mammals have been widely utilized as efficient indicators of environmental chemical pollution and its consequences due to their higher position in the food chain and long lifespan [27][28][29]. Prior research has found exposure to different phthalate compounds in varied cetacean species, including bottlenose dolphins (Tursiops truncatus [30][31][32][33][34][35][36][37]), killer whales (Orcinus orca [38]), sperm whales (Physeter macrocephalus [38]), long-finned pilot whales (Globicephala melas [38]), short-finned pilot whales (Globicephala macrorhynchus [30]), white-beaked dolphins (Lagenorhynchus albirostris [38]), harbour porpoises (Phocoena phocoena [38]), Risso's dolphins (Grampus griseus [30,31]), striped dolphins (Stenella coeruleoalba [30,31]), pygmy sperm whales (Kogia berviceps [30]), Fraser's dolphins (Lagenodelphis hosei [30]), and fin whales (Balaenoptera physalus [31]).…”
Section: Introductionmentioning
confidence: 99%